Consequence of Failure Analysis on Onshore Pipeline Based on API 581 BRD - WAYAN DIPTAGAMA (NIM 13102083), I
Transmission and distribution of oil and gas from one place to another place on land mostly conducted by onshore pipeline system. Risk of failure is always exists in every pipeline system at any operating condition. The risk is influenced by probability of failure and consequence of failure. Quantitative consequence of failure analysis is the best method to analyze the consequence of failure. This method analyzes area that affected by flammable effects, toxic, environmental damage and financial loss because of business interruption. Subsidence of soil is already occurred on pipeline system at Porong, Sidoarjo, East Java. Because of the circumstance, the pipeline system is susceptible to failure so the consequence analysis should be conducted on the pipeline system to analyze affected area and financial loss if the failure occurred. In this study, it is determined that the maximum area of equipment damage is 3646,87 ft2, while the maximum area of fatalities is 7026,9 ft2, and the maximum business interruption cost is 4557346,63 US$. All of the data is from pipeline segment Porong Offtake - Gempol freeway junction.